2021
DOI: 10.1111/ctr.14298
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the safety and preliminary efficacy of peri‐ and post‐operative treprostinil in preventing ischemia and reperfusion injury in adult orthotopic liver transplant recipients

Abstract: Background Orthotopic liver transplantation (OLT) is the only treatment option for various end‐stage liver diseases. Ischemia and reperfusion (I/R) injury is one of the unavoidable complications/conditions in OLT. In 2019, a total of 8896 livers were transplanted of which >94% organs were procured from deceased donors. An increase in the use of extended criteria donor (ECD) livers for transplantation further unraveled the role of hepatic I/R injury on short‐term and long‐term graft outcomes. Despite promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…To examine the actual clinical effect of prostacyclin, early in 2000, a placebo controlled randomized clinical trial by Neumann et al ( 61 ) showed that treatment with prostacyclin tended to lower peak AST levels and induced a significant decrease in the difference between mixed venous oxygen content and hepatic venous oxygen content (delta O 2 ) after 24 and 48 h after reperfusion, which indicated an improvement of regional hepatic-splanchnic oxygenation. To our interest, recently, a prospective, single-center, non-randomized, interventional study was performed by Almazroo et al ( 30 ) to evaluate the safety and preliminary efficacy of perioperative treprostinil in preventing IRI in adult OLT recipients. In this study, subjects showed good tolerance to the continuous infusion of treprostinil without occurrence of primary graft non-function, which achieved 100% graft and recipient survival, minimized need for ventilation support, shortened hospitalization time, and improved hepatobiliary excretion comparable to normal healthy adults.…”
Section: Contemporary Strategies and Approaches For Hepatic Irimentioning
confidence: 99%
“…To examine the actual clinical effect of prostacyclin, early in 2000, a placebo controlled randomized clinical trial by Neumann et al ( 61 ) showed that treatment with prostacyclin tended to lower peak AST levels and induced a significant decrease in the difference between mixed venous oxygen content and hepatic venous oxygen content (delta O 2 ) after 24 and 48 h after reperfusion, which indicated an improvement of regional hepatic-splanchnic oxygenation. To our interest, recently, a prospective, single-center, non-randomized, interventional study was performed by Almazroo et al ( 30 ) to evaluate the safety and preliminary efficacy of perioperative treprostinil in preventing IRI in adult OLT recipients. In this study, subjects showed good tolerance to the continuous infusion of treprostinil without occurrence of primary graft non-function, which achieved 100% graft and recipient survival, minimized need for ventilation support, shortened hospitalization time, and improved hepatobiliary excretion comparable to normal healthy adults.…”
Section: Contemporary Strategies and Approaches For Hepatic Irimentioning
confidence: 99%
“…Ischemic reperfusion injury (IRI) is defined as the functional metabolic disorder and structural destruction caused by reperfusion based on ischemic injury after the blood supply of organs and tissues [1]. Hepatic ischemia-reperfusion injury (HIRI) is a serious and harmful surgical complication, typically appearing during hepatobiliary surgery [2], liver transplantation [3] traumatic shock, and severe infection in clinical practice [4]. To date, although tremendous efforts have been made to clarify the potential underlying mechanisms that contribute to HIRI insult, the cellular and molecular events, regulating cell damage after HIRI, have still remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, no pharmacological options are currently approved for the prevention of hepatic ischemia-reperfusion injury following transplantation. A prospective, pilot, single-center, open-label, nonrandomized, dose-escalation phase I/II study in liver transplant patients investigated the efficacy of intravenous treprostinil administration in the prevention of hepatic ischemia-reperfusion with some encouraging results[ 118 ]. A small group of patients who underwent liver transplantation and received perioperative intravenous treprostinil at a dose of 5 ng/kg/min followed by postoperative contentious infusion at a dose of 2.5-5 ng/kg/min for approximately 5 d showed improved liver function and 100% graft and recipient survival at six months[ 118 ].…”
Section: Introductionmentioning
confidence: 99%
“…A prospective, pilot, single-center, open-label, nonrandomized, dose-escalation phase I/II study in liver transplant patients investigated the efficacy of intravenous treprostinil administration in the prevention of hepatic ischemia-reperfusion with some encouraging results[ 118 ]. A small group of patients who underwent liver transplantation and received perioperative intravenous treprostinil at a dose of 5 ng/kg/min followed by postoperative contentious infusion at a dose of 2.5-5 ng/kg/min for approximately 5 d showed improved liver function and 100% graft and recipient survival at six months[ 118 ]. Preliminary observations indicated a rapid reduction in transaminase plasma levels, improvement in hepatobiliary excretory function and prevention of the occurrence of acute kidney failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation